Mitotic activity of cultured human lymphocytes treated with gold nanoparticles - Hussein, Sumaiah I. (Iraqi Journal of Cancer and Medical Genetics, 2017)
Potential health and environmental effects of nanoparticles need to be thoroughly assessed before their widespread commercialization. The present investigation was planned with the aims to determine the effects of gold nanoparticles (GNPs) on blast (BI) and mitotic (MI) indices of cultured lymphocytes. The results revealed that BI (50.3 ± 2.3, 30.2 ± 1.9, 10.5 ± 0.7 and 0.0%, respectively) and MI (70.1 ± 2.9, 20.4 ± 1.1, 5.3 ± 0.1 and 0.0%, respectively) showed a gradual decreased percentage as the concentration of GNPs was increased from 0.085 to 0.66 μg/mL, and the difference was significant compared to control culture (81.6 ± 2.5 and 90.2 ± 3.7%, respectively). A maximum inhibition of BI and MI was occurred at the concentration 0.66 μg/mL. In conclusion, GNPs can be considered as a growth inhibiting agent, but it is too early to reach a final conclusion in this regard and further investigations are required to elucidate the biochemical mechanisms involved in inhibiting the mitotic activity of lymphocytes. Key word: gold nanoparticles, mitotic index, blast index, lymphocytes